2012
DOI: 10.4240/wjgs.v4.i7.177
|View full text |Cite
|
Sign up to set email alerts
|

Use of barbed suture for peritoneal closure in transabdominal preperitoneal hernia repair

Abstract: AIM:To investigate the use of the V-Loc wound closure device for transabdominal preperitoneal hernia repair. METHODS:We performed conventional transabdominal preperitoneal hernia repair in 19 patients, including one single incisional case using V-Loc. Except for the use of V-Loc for peritoneal closure, the procedures were the same as those used in conventional techniques. RESULTS:Although the operators included 2 residents who have no experience in laparoscopic herniorrhaphy and intracorporeal suture, the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…To date, the efficacy of this new material has been evaluated in different surgical fields, a few general surgery studies are available [12][13][14][15][16][17][18], gynecologists have also demonstrated its utilities [19][20][21], oncologists have reported advantages in its properties [22] and urology is the field where its usefulness is already a standard and concentrates most of its reports [23][24][25][26][27].…”
mentioning
confidence: 99%
“…To date, the efficacy of this new material has been evaluated in different surgical fields, a few general surgery studies are available [12][13][14][15][16][17][18], gynecologists have also demonstrated its utilities [19][20][21], oncologists have reported advantages in its properties [22] and urology is the field where its usefulness is already a standard and concentrates most of its reports [23][24][25][26][27].…”
mentioning
confidence: 99%
“…To date, there have been no suitable devices for peritoneal closure for beginners. 6 Small bowel obstruction after TAPP can be caused by displaced spiral tacks used for peritoneal closure, as reported by Fitzgerald et al, 19 with an incidence of 0.2 to 0.5%. Additionally, the study by Kapiris et al reported reduced complaints of persistent inguinal pain as they adopted a stable-free technique for mesh fixation and peritoneal closure.…”
Section: Discussionmentioning
confidence: 81%
“…recently, uni-or bidirectional braided, self-anchoring, and knotless sutures are frequently used and offer time-saving work. 6 But, with a risk of cut through the peritoneal flaps can occur, producing gap and internal herniation through the preperitoneal space. Some authors reported small bowel obstruction after using a self-anchoring braided suture for peritoneal closure in TAPP repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general surgery, unidirectional absorbable V-Loc® (Covidien) is used to close the peritoneum during transabdominal preperitoneal polypropylene procedures [6]. The free tail of the barbed suture could result in intestinal obstruction [7].…”
Section: Braided Synthetic Suture Materialsmentioning
confidence: 99%